1996
DOI: 10.1007/bf00019461
|View full text |Cite
|
Sign up to set email alerts
|

GBSS T-DNA inserts giving partial complementation of the amylose-free potato mutant can also cause co-suppression of the endogenous GBSS gene in a wild-type background

Abstract: The wild-type gene encoding granule-bound starch synthase (GBSS) is capable of both complementing the amylose-free (amf) potato mutant and inhibiting the endogenous GBSS gene expression in wild-type potato. Co-suppression of the endogenous GBSS gene, easily visualised by staining the starch with iodine, occurred when the full-size GBSS sequence (genomic), GBSS cDNA or even the mutant amf allele were introduced into the wild-type potato. Conversely, introduction of the GBSS promoter sequence alone, did not resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 35 publications
2
10
0
Order By: Relevance
“…Also in potato it was reported that the values of mRNA in antisense and co-suppression transformants varied, and was different within one tuber and different tubers from the same clone. The only relation which could be found was that in all antisense plants the level of mRNA was always lower than in the controls (Kuipers et al 1995;Flipse et al 1996). This was also observed in cassava.…”
Section: Discussionsupporting
confidence: 52%
“…Also in potato it was reported that the values of mRNA in antisense and co-suppression transformants varied, and was different within one tuber and different tubers from the same clone. The only relation which could be found was that in all antisense plants the level of mRNA was always lower than in the controls (Kuipers et al 1995;Flipse et al 1996). This was also observed in cassava.…”
Section: Discussionsupporting
confidence: 52%
“…Since our Wx transgene has homology with the silenced endogenous genes in both the promoter and the coding sequence it was not possible to distinguish which eect caused silencing. In the case of cosuppression of the GBSS gene in potato, it has been shown that the coding region is sucient to cause cosuppression (Flipse et al 1996). Our observation that no silencing of the transgene occurs in the mutant wx rice in which no Wx mRNA was detected might indicate the involvement of RNA in gene silencing; this is a characteristic of post-transcriptional silencing.…”
Section: Discussionmentioning
confidence: 62%
“…Many mutations of the locus are available in rice and it is one of the best-studied loci in rice (Sano 1984;Okagaki and Wessler 1988;Hirano and Sano 1991;Wang et al 1995). In potato, cosuppression of the GBSS gene occurs when either the genomic GBSS gene or the cDNA fused to the CaMV35S promoter is introduced into wild-type plants (Flipse et al 1996). It was also shown that multicopy GBSS transgenes were not only partially suppressed due to cis-interaction among them, but also caused cosuppression by acting on the wild-type gene (Flipse et al 1994;1996).…”
Section: Introductionmentioning
confidence: 99%
“…Silencing of GBSSI in potato has been achieved by introduction of either antisense or sense copies of GBSSI cDNA or genomic DNA (Visser et al, 1991a(Visser et al, , b, 1996Hofvander et al, 1992;Kuipers et al, 1992Kuipers et al, , 1994aKuipers et al, , b, 1995Kuipers et al, , 1997Kull et al, 1995;Flipse et al, 1996c). Down-regulation of GBSSI was most efficiently attained with antisense GBSSI T-DNA insertions: 50-80% of the primary antisense transformants exhibited a decrease in amylose content, compared with ca.…”
Section: Silencing Of Gbssi In Potatomentioning
confidence: 99%